Combination of Lanosterol and Nilvadipine Nanosuspensions Rescues Lens Opacification in Selenite-Induced Cataractic Rats - Saori Deguchi; Reita Kadowaki; Hiroko Otake; Atsushi Taga; Yosuke Nakazawa; Manju Misra; Naoki Yamamoto; Hiroshi Sasaki; Noriaki Nagai (MDPI AG, 2022)
It has recently been reported that lanosterol (LAN) plays a preventive role against lens opacification through the reversal of crystalline aggregation. However, the effect of LAN is not sufficient to restore lens transparency. In this study, we designed ophthalmic nanosuspensions (LAN-ONSs and NIL-ONSs) based on LAN and nilvadipine (NIL), which can counteract cataract-related factors (e.g., enhanced Ca2+ and calpain levels), and investigated whether the combination of LAN-ONSs and NIL-ONSs can restore the nuclear lens opacity in sodium-selenite-induced cataractic rats (cataractic rats). The mean particle sizes of the LAN-ONSs and NIL-ONSs were 108.8 nm and 89.0 nm, respectively. The instillation of the LAN-ONSs or NIL-ONSs successfully delivered the drugs (LAN or NIL) into the lenses of the rats, although the instillation of LAN-ONSs or NIL-ONSs alone did not increase lens transparency in the cataractic rats. On the other hand, the cataract-related factors (enhanced Ca2+ and calpain levels) were significantly alleviated by the combination of LAN-ONSs and NIL-ONSs; furthermore, the perinuclear refractile ring in the lens nucleus and enhanced number of swollen fibers were attenuated by the LAN-ONS and NIL-ONS combination. Moreover, the opacity levels in the cataractic rats were reduced after treatment with the combination of LAN-ONSs and NIL-ONSs. It is possible that the combination of LAN and NIL will be useful for the treatment of lens opacification in the future.